ARTIFICIAL INTELLIGENCE IN DISTANCE LEARNING: A NEW APPROACH FOR SOKOTO STATE TERTIARY EDUCATION - Musa, Fatima Abubakar (Ayden Multidisciplinary Research Journal, 2024)
This research study explores the potential benefits and challenges of integrating Artificial Intelligence (AI) distance education in Sokoto state tertiary institutions. The rapid advancement of AI technologies presents an opportunity to revolutionize the delivery of education, particularly in the context of distance learning. This research aims to investigate the impact of AI on personalize learning experiences, administrative efficiency and students support services in the context of Sokoto state tertiary institutions. The study employed a mixed-method approach, incorporating both quantitative and qualitative data collection methods. Survey and interviews were conducted with students, educators and administrators to gather insight into their perceptions and the experiences with AI-enabled distance education. Additionally, data analysis will be conducted to assess the effectiveness of AI tools in improving learning outcomes, automating administrative tasks and enhancing and support. The finding of this research will contribute to the existing body of knowledge on the integration of AI in distance education, with a specific focus on the unique needs and challenges faced by Sokoto state tertiary institutions. The research outcome will provide valuable insight for educational policy makers, administrators and educators seeking to leverage AI technologies to enhance the quality and accessibility of distance education in Sokoto state.